A bioarchaeological investigation of three late Chalcolithic pits at Ovçular Tepesi (Nakhchivan, Azerbaijan). (1st October 2013) - Berthon, Rémi; Decaix, Alexia; Kovács, Zsófia Eszter; Van Neer, Wim; Tengberg, Margareta; Willcox, George; Cucchi, Thomas
<x xml:space="preserve">Abstract</x> Socio-economic organisation, subsistence strategies and environmental exploitation still remain largely open questions for the Late Chalcolithic period (ca. 4500-3500 BC) in southern Caucasus even though they are of prime importance for understanding the development of post-Neolithic societies in these semi-arid and mountainous areas. Interdisciplinary bioarchaeological research can, however, provide valuable new insights into these issues. In the Late Chalcolithic occupation layers at Ovçular Tepesi (Nakhchivan Autonomous Republic, Azerbaijan), the fills of pits, composed mainly of domestic refuse, proved to contain the richest and most diverse assemblages of biological remains at the site. These remains, retrieved by the use of flotation and sieving techniques, therefore constitute ideal assemblages for understanding subsistence strategies and the exploitation of natural resources. It is shown here that the agricultural economy at Late Chalcolithic Ovçular Tepesi was based mainly on the cultivation of cereals and pulses and the herding of sheep and goat. The river and its surroundings provided wood fuel and fish. The results of the bioarchaeological study further suggest that the Late Chalcolithic village was occupied permanently as shown by the development of commensal populations of small mammals.